Study on different metal oxide with Hylocereus polyrhizus (dragon fruit) in dye-sensitized solar cells performance - Hartati Katu Mahmud (2019)
The energy crisis becomes a serious issue for every country in the world. The world‘s demand depends on the inadequate energy from resources such as oil and fossil fuel that are diminishing due to nonstop consumption. Thus, few renewable energy as unconventional energy have been explored, including solar energy. A solar cell use the energy of the sun and transforms it into electricity. Dye-sensitized solar cell (DSSC) transforms visible light energy through separation in photo-absorber layer of a wide gap semiconductor. Dye-sensitized solar cells have several layers including light absorber dye and an active electrode, in which in this study three different metal oxides of photoanode which are titanium dioxide, TiO2 (TO) nanoparticles, zinc oxide, ZnO (ZO) and aluminum oxide, Al2O3 (AO) were prepared and examined each performance in DSSC. The extraction of Hylocereus polyrhizus (dragon fruit) coated on three different metal oxides were characterized with several analysis such as UV–Vis absorption spectroscopy, scanning electron microscopy (SEM), four point probe (4PP) and electrochemical impedance spectra (EIS). It was found that Hylocereus polyrhizus extract has good absorbance and the bandgap value recorded was 2.15 eV. With dye extract coated on metal oxides (MO), the TO/DF/ITO has the lowest bandgap value which is 1.55 eV, compared to ZO/DF/ITO and AO/DF/ITO with value of 2.60 and 2.80 eV respectively. Besides, the surface morphology viewed by SEM analysis exhibited morphology of each MO/DF/ITO has different in particles sizes and surface. Results from 4PP, shows the sheet resistance values of DF/ITO, TO/DF/ITO, AO/DF/ITO and ZO/DF/ITO are 26.69, 13.78, 23.39 and 18.58 Ωm respectively. The conductivity values of DF/ITO, TO/DF/ITO, AO/DF/ITO and ZO/DF/ITO are 3.75E-04, 7.26E-04, 4.28E-04 and 5.38E-04 Scm-1, respectively while power conversion efficiency (PCE) TO/DF/ITO performed the highest with 5.20 % followed with ZO/DF/ITO, AO/DF/ITO and DF/ITO with 4.35 %, 3.32 % and 1.58 %, respectively.